The Infantile spasm, clinical manifestation of a rare brain tumor: a case report and review in literature - babaei, meisam; Morteza; Amin; Ehsan; Rezvan; Mahnaz (Iranian Journal of Child Neurology, 2022)
Desmoplastic infantile ganglioglioma (DIG) has a favorable prognosis; and is classified as a benign infantile brain tumor; it is more common in children under 2 years of age. In this report, we introduce one 5.5 months-old infant who was referred with infantile spasm and was diagnosed with a brain tumor. EEG showed modified hypsarrhythmia. The patient underwent ACTH treatment and was asked for a brain MRI. MRI of the patient’s brain showed large heterogeneous masses in the right hemisphere with shifting to other side. The patient underwent surgery. The extra-axial mass was completely resected, and the diagnosis of DIG grade I confirmed with the pathology. At present, the patient is only on phenobarbital, and the seizures do not recur, and the general condition is good; also, the growth of the patient’s head and development is normal for age. We found 13 reported cases during the search, of which 9 were boys and 4 were girls. The mean age of tumor diagnosis from the onset of symptoms was between 2 weeks to two months. Of 13 patients, in 8 patients, the origin of the mass was the right hemisphere. The most common tumors observed were glioma (4 patients), Hamartoma hypothalamus (3 patients). Except for three patients who died, the remaining patients found complete recovery with complete control of seizures after the mass’s surgical resection.